Assessing the susceptibility of amylose–lysophosphatidylcholine complexes to amylase by the use of iodine. Issue 5 (2nd December 2013) - Ahmadi‐Abhari, Salomeh; Woortman, Albert J. J.; Hamer, Rob J.; Loos, Katja
<x xml:space="preserve">Abstract</x> The formation of amylose–lysophosphatidylcholine (LPC) inclusion complexes renders amylose less susceptible to amylase digestion. In order to better understand this phenomenon on a structural level, the complexation of 9% wheat starch suspensions with 0, 2, 3, and 5% exogenous LPC was developed in RVA. Amylose–LPC inclusion complexes were isolated after 15, 30, 60, 120, and 240 min in vitro digestion of the wheat starch suspensions to quantify the amount of non‐complexed amylose by spectrophotometry. The samples were dissolved in DMSO containing 0.5% LiBr and exposed to iodine. In addition, parts of the digesta were defatted and subjected to the same procedure to elucidate the total amount of amylose that remained undigested. In this way, more insight was obtained into the protective effect of amylose–LPC complex formation on digestion of starch. This study confirms that the amylose susceptibility to amylolysis decreases in the presence of LPC. Higher LPC concentrations not only induced the formation of more amylose inclusion complexes but also resulted in more stable complexes which remained undigested as well as longer amylose chains after enzyme hydrolysis, due to the presence of LPC inside the amylose helix. In addition, a higher melting enthalpy of the amylose–LPC complexes in the digesta demonstrates the protective effect of LPC during enzyme hydrolysis.